HUBUNGAN ASUPAN MAKANAN, KEANEKARAGAMAN PANGAN, DAN LAMA TIDUR DENGAN PERSEN LEMAK TUBUH PADA ANAK SEKOLAH DASAR (Studi di SD Hj. Isriati Baiturrahman 1 Semarang Tahun 2017) - Yuni Atika Sari; M. Zen Rahfiludin; Martha Irene Kartasurya; Ronny Aruben (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
The incidence of obesity on elementary school students of Hj. Isriati Baiturrahaman 1 Semarang in 2010 ranged from 49.9% with increasing a tendency of increasing. Obesity in children may continue in adulthood. The purpose of this study was to analyze the correlations between food intake, sleep duration, and food diversity with body fat percentage in elementary school children. This study was an observational study with a cross sectional design. The study population was of grade 4 and 5 primary school students (182 students). A total of 58 students were selected by Purposive Sampling. Data collection was conducted with 2x24 hours food recall, food diversity table, anthropometric measurements and body fat percentage using BIA (Bioelectrical Impedance Analysis). Data were analysed by Spearman and Pearson Rank Correlation test. The results showed that 44.5% of male students were obese and 9.8% of female students were obese. Energy sufficiency level was excessive on 87,9%, 37.9% of students had excess carbohydrate intake, 62.1% students had high saturated fat intake, 24.1% of students had high intake of unsaturated fat, 43.1% of the subjects had low food diversity index. The results show that there were positive correlations between energy consumption level (p = 0,00), and food diversity (p = 0,00) with body fat percentage. It was concluded that obesity in these children is associated with high energy consumption and food diversity.